Recycle Crushed Brick as Road Base Material - MAT DIN, AHMAD LUQMANUL HAKIM; ABDULLAH, MOHD SUFYAN (Progress in Engineering Application and Technology, 2021)
The demand for natural resources lead to environmental problems. In addition, construction activity always generated a lot of solid waste especially brick, masonry and aggregate. Therefore, implementation of recycle crushed brick (CB) as road base material must provide sufficient working load to support the vehicles. This paper is to study properties of CB and to identify the optimum percentage of CB as partial replacement of road base materials. This study is focusing on partial replacement of CB and natural aggregate (NA). The percentage replacement of CB is 10%, 15%, 20%, 25%, 30% and 100%. Meanwhile, experiments that carried out on the specimens are aggregate compaction, water absorption and density test and California bearing ratio (CBR). The data is collected from previous study. 10% CB replacement shows the best and acceptable amount to be used in real situation.